2013
DOI: 10.1080/09658211.2012.713971
|View full text |Cite
|
Sign up to set email alerts
|

Sex, cheating, and disgust: Enhanced source memory for trait information that violates gender stereotypes

Abstract: The present study examines memory for social-exchange-relevant information. In Experiment 1 male and female faces were shown together with behaviour descriptions of cheating, altruistic, and neutral behaviour. Previous results have led to the hypothesis that people preferentially remember schema-atypical information. Given the common gender stereotype that women are kinder and less egoistic than men, this atypicality account would predict that source memory (that is, memory for the type of context to which a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
84
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(98 citation statements)
references
References 50 publications
10
84
4
Order By: Relevance
“…In the memory test, old–new recognition was not affected by facial trustworthiness and partner behavior, consistent with a large number of previous studies showing that a person’s behavior has no effect on old–new face recognition (e.g., Barclay and Lalumière, 2006; Mehl and Buchner, 2008; Buchner et al, 2009; Kroneisen and Bell, 2013). There are some reports suggesting that old–new recognition is better for untrustworthy-looking than for trustworthy-looking persons (Rule et al, 2012; Bell et al, 2013; Mattarozzi et al, 2015), but this finding was not reliably obtained across experiments (Bell et al, 2012b), and was not replicated here.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the memory test, old–new recognition was not affected by facial trustworthiness and partner behavior, consistent with a large number of previous studies showing that a person’s behavior has no effect on old–new face recognition (e.g., Barclay and Lalumière, 2006; Mehl and Buchner, 2008; Buchner et al, 2009; Kroneisen and Bell, 2013). There are some reports suggesting that old–new recognition is better for untrustworthy-looking than for trustworthy-looking persons (Rule et al, 2012; Bell et al, 2013; Mattarozzi et al, 2015), but this finding was not reliably obtained across experiments (Bell et al, 2012b), and was not replicated here.…”
Section: Discussionsupporting
confidence: 88%
“…In most experiments (Suzuki and Suga, 2010; Bell et al, 2012b), this memory advantage was asymmetric in that participants remembered cheating better than cooperation when the partners looked trustworthy, but there was only a non-significant tendency toward remembering cooperation better than cheating when the partners looked untrustworthy. This asymmetry should be particularly pronounced for female faces because they elicit more positive social expectations than male faces, which means that the violation of these positive expectations is particularly salient when female faces are used (Kroneisen and Bell, 2013). …”
Section: Methodsmentioning
confidence: 99%
“…In previ ous studies (Kroneisen & Bell, 2013), it was observed that people expect men to show more disgusting behaviors than women. These stereotypes may have some truth in them, because there is evi dence that men indeed are more likely to show disgusting behavior than women (Rozin, Haidt, McCauley, Dunlop, & Ashmore, 1999).…”
Section: Methodsmentioning
confidence: 97%
“…Overview of the procedure common to all experiments.^ Consistent with the sex stereotype that women are kinder and less egoistic than men(Kroneisen & Bell, 2013), female faces (trustworthy looking: M [SD] = 2.75 [0.15], untrustworthy looking: 1.88 [0.11]) were rated as significantly more trustworthy than male ones (trustworthy looking: 2.59 [0.12], untrustworthy looking: 1.68 [0.07]), F(l, 20) = 13.684, MSE = 0.013,/> = .001, f\j = .…”
mentioning
confidence: 96%